2016
DOI: 10.3906/tar-1504-95
|View full text |Cite
|
Sign up to set email alerts
|

Identification of olive cultivars using image processing techniques

Abstract: As a country in an olive production zone, olive (Olea europaea L.) production is of great economic importance for Turkey. Turkey has 88 domestic and 28 foreign cultivars of olive, all of which are located in the Kemalpaşa Production and Research Garden (Olive Gene Bank) at the Olive Research Station in İzmir (38°25′34.7628″N, 27°25′22.9872″E). The aim of this study was the identification of olive cultivars using image processing techniques. For this aim, images of olives, taken at 2896 × 1944 pixel and 300 dpi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 10 publications
(18 reference statements)
0
11
0
Order By: Relevance
“…Turkey has 88 domestic and 28 foreign cultivars of olive Beyaz and Öztürk. [ 22 ] Kaya et al. [ 23 ] after making the assessment of the genetic relationship of the Turkish olives ( Olea europaea subsp europaea ) based on the cpDNA trnL‐F regions of their genes, reported that the Turkish olive cultivars demonstrated a low level of genetic variation in terms of cpDNA trnL‐F regions and concluded that this may indicate the genetic stability of plastid genomes.…”
Section: Methodsmentioning
confidence: 99%
“…Turkey has 88 domestic and 28 foreign cultivars of olive Beyaz and Öztürk. [ 22 ] Kaya et al. [ 23 ] after making the assessment of the genetic relationship of the Turkish olives ( Olea europaea subsp europaea ) based on the cpDNA trnL‐F regions of their genes, reported that the Turkish olive cultivars demonstrated a low level of genetic variation in terms of cpDNA trnL‐F regions and concluded that this may indicate the genetic stability of plastid genomes.…”
Section: Methodsmentioning
confidence: 99%
“…As there is plethora of olive varieties with a diversity of morphological and physiological characteristics, the existence of many different qualities is expected [19]. In order to avoid olive adulterations, several discriminant protocols for varietal identification, based on stone, fruit, and leaf data have been used [20].…”
Section: Introductionmentioning
confidence: 99%
“…Several advanced analytical techniques have been used for the study of authentication of table olives, such as high-performance liquid chromatography (HPLC) [23,28], ultra-highperformance liquid chromatography-quadrupole time of flight tandem mass spectrometry (UHPLC-QTOF-MS) [25], gas chromatography-mass spectrometry (GC-MS) [26] and nuclear magnetic resonance spectroscopy (NMR) [21]. Chemometrics is an important science which has been extensively used in food science and authenticity studies to facilitate interpretation of huge load of data, and it provides an easy way to visualize the samples [19,20,[29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there are also some product-based classification studies conducted by taking apple, banana, pear, pineapple, grape, melon, watermelon, citrus and avocado fruit into consideration (Zhang and Wu, 2012;Zhang et al, 2014). Variety based studies have been conducted to classify varieties of wheat (Dubey et al, 2006;Marini et al, 2008;Arefi et al, 2011;Pazoki and Pazoki, 2011;Zapotoczny, 2011;Khoshroo et al, 2014;Taner et al, 2015), rice (Liu et al, 2005;Guzman and Perelta, 2008;Silva and Sonnadara, 2013;Pazoki et al, 2014), barley (Zapotoczny, 2012), corn (Chen et al, 2010), bean (Nasirahmadi and Behroozi-Khazaei, 2013), and olive (Beyaz and Öztürk, 2016;Beyaz et al, 2017). Taner et al (2018) conducted both product and variety-based classification and in their study, they conducted with bread wheat, durum wheat, barley, oat and triticale products.…”
Section: Introductionmentioning
confidence: 99%